The evolution of gas-phase metallicity and resolved abundances in star-forming galaxies at z ≈ 0.6 – 1.8 - Gillman, S; Tiley, AL; Swinbank, AM; Dudzevičiūtė, U; Sharples, RM; Smail, I; Harrison, CM; Bunker, AJ; Bureau, M; Cirasuolo, M; Magdis, GE; Mendel, T; et al. (Oxford University Press, 2020)
We present an analysis of the chemical abundance properties of ≈650 star-forming galaxies at z ≈ 0.6 – 1.8. Using integral-field observations from the K - band Multi-Object Spectrograph (KMOS), we quantify the [N II]/Hα emission-line ratio, a proxy for the gas-phase Oxygen abundance within the interstellar medium. We define the stellar mass – metallicity relation at z ≈ 0.6 – 1.0 and z ≈ 1.2 – 1.8 and analyse the correlation between the scatter in the relation and fundamental galaxy properties (e.g. Hα star-formation rate, Hα specific star-formation rate, rotation dominance, stellar continuum half-light radius and Hubble-type morphology). We find that for a given stellar mass, more highly star-forming, larger and irregular galaxies have lower gas-phase metallicities, which may be attributable to their lower surface mass densities and the higher gas fractions of irregular systems. We measure the radial dependence of gas-phase metallicity in the galaxies, establishing a median, beam smearing-corrected, metallicity gradient of ΔZ/ΔR= 0.002 ± 0.004 dex kpc−1, indicating on average there is no significant dependence on radius. The metallicity gradient of a galaxy is independent of its rest-frame optical morphology, whilst correlating with its stellar mass and specific star-formation rate, in agreement with an inside-out model of galaxy evolution, as well as its rotation dominance. We quantify the evolution of metallicity gradients, comparing the distribution of ΔZ/ΔR in our sample with numerical simulations and observations at z ≈ 0 – 3. Galaxies in our sample exhibit flatter metallicity gradients than local star-forming galaxies, in agreement with numerical models in which stellar feedback plays a crucial role redistributing metals.